TINGKAT PENDIDIKAN DAN STATUS EKONOMI DENGAN MINAT MENGGUNAKAN GIGI TIRUAN SEBAGIAN LEPASAN PADA PRA LANSIA - Nur Al Fisyahri; Suharyono Suharyono; Siti Hidayati (Journal of Oral Health Care, 2014)
Dental health is one thing that is faced by older people notto mention pre elderly. Loss of teeth and toothless state inpre elderly age prevalence tends to decrease, but the conditionis still quite high in developing countries are associatedwith economic conditions and low education . It isexpected to also affect a person’s interest to replace missingteeth with denture. This study aims to prove the relationshipbetween level of education and economic statusof the interest in using removable partial dentures .The research is an analytic survey with cross sectionaldesign and farms located in Tambak Bayan Sleman District.The sampling technique performed in this study ispurposive sampling. Sample is 31 pre elderly people whohave lost at least 2 teeth but not wear dentures . Pre elderlywho meet the criteria are given an explanation of how to fillout a questionnaire, and then were instructed to fill outquestionnaires about their level of education, economicstatus, and interests using removable partial dentures .Average pre elderly in Tambak Bayan Sleman District pondsecondary education ( high school ) is 48.4% , ie economicstatus was 51,6 % , and has a keen interest inusing removable partial dentures is 48.4 % .Data analysisusing statistical test and the Kendall - Tau showed that therelationship of education with an interest rate using removablepartial dentures have a significance of 0.012 ,while the relationship between the economic status of theinterest in using removable partial dentures have a significanceof 0.001 . This indicates that the value of p < 0.05means that Ho is rejected , so that there is a significantcorrelation between level of education and economic statusof the interest using removable partial dentures on preelderly.